Γνωστά και άγνωστα ιστορικά έργα της Τουρκοκρατίας σε χειρόγραφο κώδικα του Νικολάου Καρατζά - Παΐζη–Αποστολοπούλου, Μάχη (The Gleaner, 2011)
KNOWN AND UNKNOWN HISTORICAL TEXTS REGARDING THE OTTOMAN PERIOD FOUND IN A MANUSCRIPT OF NIKOLAOS KARATZAS MS 5 of the Kourilas Collection, now preserved at the University of Ioannina, contains 41 historical texts concerning mainly the history of the Ottoman Empire during the 17th and 18th centuries. The manuscript was written by the eminent 18th-century collector and scholar Nikolaos Karatzas. Many of the texts are unedited. This preliminary study includes a list of these texts, their incipits and some paleographical notes. MACHI PAIZI-APOSTOLOPOULOU